(untitled) (Journal on Excellence in College Teaching, 2024)
The authors, members of a faculty learning community (FLC) within the College of Health and Human Development at California State University, Northridge, surveyed faculty participants to assess the perceived impact of the FLC on faculty members’ ability to strengthen faculty-student relationships and student success, particularly among Latino students. The participants identified improvements in mentoring, increased awareness of cultural issues related to Latino students, greater knowledge of available campus resources, and a stronger sense of faculty support. These findings suggest that faculty development programs like FLCs may equip faculty with knowledge and strategies to help close the college completion gap for Latinos.